30 years of Ukraine's polar research in Antarctica and the Ukrainian Antarctic Journal - Vitaliy Starostenko (Ukrainian Antarctic Journal, 2024)
The article briefly presents the history of the Ukrainian Antarctic  Akademik Vernadsky station, the beginning and the current state of Antarctic scientific research in Ukraine in the Antarctic Peninsula. It also provides information on the contribution of the scientific publication Ukrainian Antarctic Journal to the dissemination of the results of Antarctic research from the area of ​​the Akademik Vernadsky station.